Process Parameters Optimization for Quality Banana Fiber Extraction Using Mechanical Decorticator - Adhikari, Pratik; Devkota, Lochan; Dhungana, Bibek (International Journal of Applied Sciences and Biotechnology, 2026)
Natural fibers can be spun into threads and can be used for various applications, as these are more sustainable than synthetic fibers. Banana pseudo-stem is considered agricultural waste after harvest and is left to rot in the fields that can be used as a valuable natural fiber source for composite as well as textile industries. Looking at the current extraction processes, the quality of fibers is observed to be inferior in the case of mechanical extraction when compared with manual traditional methods. This study focuses on this problem and investigates the banana fiber extraction machine and its process parameters optimization. The effect of blade profiles in the fiber extraction was evaluated using an after designing decorticator-type fiber extraction machine. The effective resistive force was observed to be 22.194 N, and the power was 174.308 W. It is observed that the optimum speed is 640 rpm and 2mm clearance for sharp-edged blades and 1mm for chamfered edged, with chamfered edges being able to produce high-quality fiber that is close to manual fiber quality.Int. J. Appl. Sci. Biotechnol. Vol 14(1): 53-58.